Pengaruh Kemitraan SRC (Sampoerna Retail Community) dan Digitalisasi Pelayanan Terhadap Loyalitas Pelanggan di Toko Src Rohayati Desa Cibungur Kecamatan Parungponteng - Siti Alpinah; Agung Pramudya (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research is motivated by the importance of increasing customer loyalty in traditional retail businesses amidst increasingly competitive conditions. The Sampoerna Retail Community (SRC) Partnership Program and service digitalization are strategies implemented to increase store competitiveness by strengthening partnerships and utilizing digital technology in customer service. This study aims to determine the status of the SRC Partnership, service digitalization, and customer loyalty. It also analyzes the influence of the SRC Partnership and service digitalization, both partially and simultaneously, on customer loyalty at the SRC Rohayati Store in Cibungur Village, Parungponteng District. This research uses quantitative methods with descriptive and verification approaches. The population in this study was customers of the SRC Rohayati Store in Cibungur Village, with a sample of 110 respondents. Data collection techniques included questionnaires, observation, documentation studies, and literature review. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) program through instrument testing, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing using t-tests and F-tests. The results of the verification analysis indicate that the SRC Partnership has a positive and significant effect on customer loyalty, service digitalization has a positive and significant effect on customer loyalty, and that the SRC Partnership and service digitalization simultaneously have a positive and significant effect on customer loyalty at the SRC Rohayati Store in Cibungur Village, Parungponteng District.